Desiring the kingdom : worship, worldview, and cultural formation - Smith, James K. A., 1970- (Grand Rapids, MI : Baker Academic, 2009)
Desiring the Kingdom focuses education around the themes of liturgy, formation, and desire. The author contends--as did Augustine--that human beings are "desiring agents"; in other words, we are what we love. Postmodern culture, far from being "secular," is saturated with liturgy, but in places such as malls, stadiums, and universities. While these structures influence us, they do not point us to the best of ends. Smith aims to move beyond a focus on "worldview" to see Christian education as a counter-formation to these secular liturgies. His ultimate purpose is to re-vision Christian education as a formative process that redirects our desire toward God's kingdom and its vision of flourishing. --from publisher descriptioin
Introduction: Beyond "perspectives" : faith and learning take practice. Making the familiar strange : a phenomenology of cultural liturgies -- The end of Christian education : from worldview to worship (and back again) -- Elements of a theology of culture : pedagogy, liturgy, and the church -- Desiring, imaginative animals : we are what we love. Homo liturgicus : the human person as lover -- From thinking things to liturgical animals -- From worldviews to social imaginaries -- From spheres to aims : liturgical institutions -- Love takes practice : liturgy, formation, and counter-formation. Thick and thin practices : ritual forces of cultural formation -- Formation, mis-formation, and counter-formation : liturgies secular and Christian -- Lovers in a dangerous time : cultural exegesis of "secular" liturgies. "Reading" culture through the lens of worship -- Consuming transcendence : worship at the mall -- Sacrificial violence : the "military-entertainment complex" -- Excursus : on patriotism -- Cathedrals of learning : liturgies of the university -- Apologetic excursus : the persisting witness of idolatry -- Desiring the kingdom : the practiced shape of the Christian life. From worship to worldview : Christian worship and the formation of desire -- The primacy of worship to worldview -- The sacramental imagination : resisting naturalism and supernaturalism -- Excursus : the shape of Christian worship -- Practicing (for) the kingdom : an exegesis of the social imaginary embedded in Christian worship. Liturgical time : rhythms and cadences of hope -- Call to worship : an invitation to be human -- God's greeting and mutual greetings : hospitality, community, and graced dependence -- Song : hymning the language of the kingdom -- The law : order, norms, and freedom for the good -- Confession and assurance of pardon : brokenness, grace, hope -- Baptism : initiation into a royal priesthood, constitution of a new people -- The creed : situating belief -- Prayer : learning the language of the kingdom -- Scripture and sermon : renarrating the world -- Eucharist: supper with the King -- Offering : kingdom economics of gratitude -- Sending as witnesses : the cultural mandate meets the Great Commission -- Worship, discipleship, and discipline : practices beyond Sunday -- A Christian university is for lovers : the education of desire. A new monasticism for the university : why Christian colleges should corrupt the youth -- Christian education takes practice : three "monastic" opportunities -- Christian worship as faculty development : from Christian scholars to ecclesial scholars.
Includes bibliographical references and indexes.
Keywords: Liturgics; Christianity and culture; Liturgical adaptation; Christianity -- Philosophy